Sistem Informasi Program Pelaporan ISPA di Kota Surabaya - Nur Fauzia Laily Mubarokah; Hari Basuki Notobroto; Primayanti Primayanti (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
Acute Respiratory Infections (ARI) is a disease that occurs in many developing countries and also on the list of 10 most diseases in hospitals. This study aims to analyze the information system of ARI Reporting Program in Surabaya. Reporting on ARI cases is a surveillance of the disease. If many cases reported, it is better than only a few cases reported. This research is a descriptive study with a qualitative approach. Based on the results of the interview with the informant, it was stated that the ARI reporting program had helped in recording ARI cases that occurred in Surabaya. File formats that are still manual and not integrated with the internet (online) make sending reports longer. Even if you implement an integrated online, data entry only needs to be done once so that the same data will be stored electronically and can be sent and processed. In addition, in the excel file ARI reporting program, there are several output menus that can be used as a result of the description of ARI cases. However, the output was underutilized so that less case monitoring was implemented to reduce the number of ARI / Pneumonia cases that occurred in Surabaya. The conclusion is the ARI reporting program is very helpful in the process of data collection of ARI cases, but it would be better if they use the type of online computerization management and better utilize the graphical output of the ARI reporting program.